1991
DOI: 10.1002/ajim.4700190609
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities among nurses occupationally exposed to antineoplastic drugs

Abstract: The effect of handling antineoplastic drugs was examined in 42 nurses working in an oncology department, and the same number of nurses not exposed to antineoplastic drugs acted as controls. The exposure effect was evaluated by analysis of sister chromatid exchanges (SCE) incidence and structural chromosomal abnormalities. SCE as well as chromosomal abnormalities in the exposed group were increased (p less than 0.001 and p less than 0.01, respectively). Sign test for paired sample was used for statistical asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 19 publications
(4 reference statements)
0
16
0
2
Order By: Relevance
“…Literature reports dealing with genotoxic effects in peripheral leukocytes of healthcare workers handling antineoplastic agents are somewhat contradictory. Some studies have found an association between increase in sisterchromatid exchanges (SCE) [Sardas et al, 1991;GoloniBertollo et al, 1992], micronuclei (MN) [Yager et al, 1988;Anwar et al, 1994;Machado-Santelli et al, 1994], chromosome aberrations (CA) [Milkovic-Kraus and Horvat, 1991;Goloni-Bertollo et al, 1992;Grummt et al, 1993;Anwar et al, 1994], premature centromere division [Major et al, 1999], and DNA damage [Ü ndeger et al, 1999] and chronic exposure to these drugs. On the other hand, others have not observed any cytogenetic effect related to exposure [Benhamou et al, 1988;Cooke et al, 1991;Roth et al, 1994;Brumen et al, 1995;Ensslin et al, 1997;Lanza et al, 1999;Hessel et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Literature reports dealing with genotoxic effects in peripheral leukocytes of healthcare workers handling antineoplastic agents are somewhat contradictory. Some studies have found an association between increase in sisterchromatid exchanges (SCE) [Sardas et al, 1991;GoloniBertollo et al, 1992], micronuclei (MN) [Yager et al, 1988;Anwar et al, 1994;Machado-Santelli et al, 1994], chromosome aberrations (CA) [Milkovic-Kraus and Horvat, 1991;Goloni-Bertollo et al, 1992;Grummt et al, 1993;Anwar et al, 1994], premature centromere division [Major et al, 1999], and DNA damage [Ü ndeger et al, 1999] and chronic exposure to these drugs. On the other hand, others have not observed any cytogenetic effect related to exposure [Benhamou et al, 1988;Cooke et al, 1991;Roth et al, 1994;Brumen et al, 1995;Ensslin et al, 1997;Lanza et al, 1999;Hessel et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…U Hrvatskoj (58,67,69,72,78,79) to je donedavno bila i jedina metoda koja se izvodila kao dodatna pretraga u okviru zdravstvenih pregleda medicinskog osoblja izloženog antineoplasticima. Iz grafičkog prikaza (slika 6) vidljivo je da je broj istraživanja, koja su primjenom SCE utvrdila pozitivne i negativne rezultate, sličan.…”
Section: Izmjene Sestrinskih Kromatida (Sce)unclassified
“…Do danas su objavljeni rezultati brojnih istraživanja (tablica 3), uključujući i nekoliko provedenih u Hrvatskoj (58,69,79,84). Iz odnosa broja istraživanja koja su prikazala pozitivne ili negativne rezultate dobivene primjenom CA (slika 6) vidljivo je da je važnost ove metode u otkrivanju genotoksičnih učinaka antineoplastika nešto manja negoli je važnost analize SCE.…”
Section: Oštećenja (Aberacije) Kromosomaunclassified
“…The frequency of menstrual irregularities and amenorrhea is higher among nurses manipulating these agents (10) . Spontaneous abortions can occur, mainly during the first three months of pregnancy, besides chromosome alterations and congenital malformations (1,5,(11)(12) . Other manifestations include skin, mucous and eye irritations; hair fall and decreased immunological resistance, increased drug resistance, pharyngitis, hoarseness, herpes and cancer (13) .…”
Section: Sample Characteristicsmentioning
confidence: 99%